Leyla - Ghadami, Amin (Iran : Ghadami, Amin, 2006)
In Dec. 2003 Bam, an Iranian city, was hit by an earthquake. In this film Mohammad Akbari tells the story of his sister, Leyla and her family who died under the ruins of their house in the earthquake.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films